Translanguaging in the Multilingual Montreal Hip-Hop Community: Everyday Poetics as Counter to the Myths of the Monolingual Classroom - Low, Bronwen; Sarkar, Mela (Heteroglossia as Practice and Pedagogy, 2014)
This chapter explores the possibilities multilingual hip-hop offers for language instruction within multiethnic classrooms in Montreal shaped by multiple discursive practices. The authors review current research on multilingualism and teaching and propose strategies for overcoming the French prescriptivist monolingual mindset in education in Quebec. They also turn to poetics, and in particular the literary theory of Edouard Glissant (Caribbean discourse, 1989; Poetics of relation, 1997) and the Martinican school of Créolité, offering possibilities for rethinking relationships between oral and written, vernacular and standard language forms and for igniting language teachers’ pedagogic imaginations.
Keywords: Creolization; Hip-hop; Oraliture; Popular culture